'Turtle watching': A strategy for endangered marine turtle conservation through community participation in Sri Lanka. (January 2016) - Rathnayake, Rathnayake Mudiyanselage Wasantha
Abstract: Turtles at the Rekawa sanctuary in Sri Lanka are under threat due to ongoing illegal activities. This study estimates the entrance fee that can be charged to visitors for 'turtle watching' to ascertain whether revenues from such fees can be used to compensate fishermen and reduce such illegal activities. We carried out a contingent valuation study to examine the foreign and local visitors' willingness to pay (WTP) for turtle conservation under two different management scenarios. The estimated mean WTP per visit for local visitors was LKR 93 (USD 0.73) and LKR 143 (USD 1.12) for Scenarios 1 and 2, respectively, while the mean WTP of foreign visitors was USD 15 and USD 19 for Scenarios 1 and 2, respectively. These results, which suggest potentially huge gains in revenue, can be used to re-design entry fees for the Rekawa sanctuary and secure the cooperation of low-income fishermen in turtle conservation. Graphical abstract: Highlights: Community based tourism is a tool for coastal natural resources conservation. Community participation is an important factor in coastal resources management. Non-marketed services could be useful for natural resources conservation and livelihood development.